Avaliação de calibração de redes hidráulicas usando o método iterativo do gradiente hidráulico alternativo (MIGHA) aplicado a escoamento transiente - Rocha, Valder Adriano Gomes de Matos (2013)
The real behavior of a Water distribution System depends on precise knowledge of physical parameters such as diameter, roughness, flow consumption (demands), etc. These parameters commonly change with time. For instance, one of the main parameters, the real roughness, tend to increase with time due to degradation of the specific pipe material. One can not precisely determine the real roughness of a pipe by using direct measurement methods. In order to achieve the objective of estimating roughness with some precision, two parameters of the water distribution network should be measured in the field, these parameters are pipe flow and pressure. Once known these parameters for a reasonable amount of points, equally distributed along the network of pipes, the real roughness may be determined by inverse methods. This process is called calibration. This study proposes a methodology to determine pipe roughness using transient pressure data which occurs during the Water Hammer Analysis phenomena. The Iterative Hydraulic Gradient Method is used as the inverse method in this study. The transient pressure data is produced by changes in the flow caused by opening and closing of Control Valves. According to results presented in this study the new methodology proposed appears to be simple and which produces reliable results